Update on the Potential of Punica granatum L. Traditional Uses and Pharmacological Uses: A Review - Abdulrahman Mahmoud Dogara; Harmand A. Hama; Dogan Ozdemir (Advances in Pharmacological and Pharmaceutical Sciences)
Since the dawn of civilization, humans have turned to plants as a reliable source of safe and efficient treatment for a wide variety of medical conditions. The medicinal value of Punica granatum has been recognized for some time. Inflammation, diabetes, parasitic infections, cancer, and many other diseases have all been treated with its components. This review provides a comprehensive overview of the current biological data (those from 2018 to 2023 are included in the preclinical studies while articles of clinical studies have no limit due to their scarcity) and explores the potential applications of P. granatum as a novel platform for treating various disease conditions. Electronic searches for scholarly articles were performed using Elsevier, Springer, Google Scholar, Taylor & Francis, PubMed, and Scopus. Research the following terms: “Punica granatum,” “chemical composition,” “antioxidant,” “antibacterial,” “anti-diabetic,” “anticancer,” and other relevant terms. It has been scientifically proven that the fruit peel exhibits antioxidant, anti-inflammatory, antimicrobial, antiparasitic, antidiabetic, hepatoprotective, nerve-recovery, antihypertensive, anti-asthma, wound healing, and anticancer activities. Based on both preclinical and clinical experimentation on P. granatum, there is considerable evidence that supports the use of P. granatum extract as therapeutic agent for different ailments. The review paved the ground to precursor evidence of P. granatum extract benefits with its antioxidant, anti-inflammatory, antimicrobial, and antidiabetic properties. Furthermore, clinical trials stand out as a substrate supporting these effects with the enhancements of ailments including post menstrual, menstrual pain, semen quality, knee joint arthritis, and cardiovascular-related diseases. Nonetheless, more controlled large-scale clinical trials are needed for all the conditions to determine the effectiveness and risk benefit profile of P. granatum extract for these diseases.